Formulation studies of InhA inhibitors and combination therapy to improve efficacy against Mycobacterium tuberculosis. (December 2016) - Knudson, Susan E.; Cummings, Jason E.; Bommineni, Gopal R.; Pan, Pan; Tonge, Peter J.; Slayden, Richard A.
Summary: Previously, structure-based drug design was used to develop substituted diphenyl ethers with potency against the Mycobacterium tuberculosis (Mtb) enoyl-ACP reductase (InhA), however, the highly lipophilic centroid compound, SB-PT004, lacked sufficient efficacy in the acute murine Mtb infection model. A next generation series of compounds were designed with improved specificity, potency against InhA, and reduced cytotoxicity in vitro, but these compounds also had limited solubility. Accordingly, solubility and pharmacokinetics studies were performed to develop formulations for this class and other experimental drug candidates with high logP values often encountered in drug discovery. Lead diphenyl ethers were formulated in co-solvent and Self-Dispersing Lipid Formulations (SDLFs) and evaluated in a rapid murine Mtb infection model that assesses dissemination to and bacterial burden in the spleen. In vitro synergy studies were performed with the lead diphenyl ether compounds, SB-PT070 and SB-PT091, and rifampin (RIF), which demonstrated an additive effect, and that guided the in vivo studies. Combinatorial therapy in vivo studies with these compounds delivered in our Self-Micro Emulsifying Drug Delivery System (SMEDDS) resulted in an additional 1.4 log10 CFU reduction in the spleen of animals co-treated with SB-PT091 and RIF and an additional 1.7 log10 reduction in the spleen with animals treated with both SB-PT070 and RIF.